2018
DOI: 10.1021/acs.langmuir.8b00437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cavity Size of Mesoporous Silica on Short DNA Duplex Stability

Abstract: We studied the stabilities of short (4- and 3-bp) DNA duplexes within silica mesopores modified with a positively charged trimethyl aminopropyl (TMAP) monolayer (BJH pore diameter 1.6-7.4 nm). The DNA fragments with fluorescent dye were introduced into the pores, and their fluorescence resonance energy transfer (FRET) response was measured to estimate the structuring energies of the short DNA duplexes under cryogenic conditions (temperature 233-323 K). The results confirmed the enthalpic stability gain of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The observed temperature and hydration effects on adsorption are of practical importance. Adsorption of phosphate groups, , pharmaceutical substances, , and DNA on silica, removal of impurities from polluted water, and environmental safety of sediments , are humidity-sensitive. Another potentially important type of guests are molecules, which exhibit self-assembling ability in aqueous solutions. Such molecules have remained outside the scope of this work.…”
Section: Discussionmentioning
confidence: 99%
“…The observed temperature and hydration effects on adsorption are of practical importance. Adsorption of phosphate groups, , pharmaceutical substances, , and DNA on silica, removal of impurities from polluted water, and environmental safety of sediments , are humidity-sensitive. Another potentially important type of guests are molecules, which exhibit self-assembling ability in aqueous solutions. Such molecules have remained outside the scope of this work.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal stabilities of simple secondary structures of DNA confined inside amine-functionalized mesoporous silica pores were examined. [115][116][117] The results indicated that short-DNA duplexes were stabilized by confinement inside aminefunctionalized cylindrical silica pore channels (BJH pore diameter, 1.6 to 7.4 nm). 115,116 Particularly, short-DNA duplexes confined inside the size-matched pores (BJH pore diameter: 1.6 and 2.3 nm) were significantly stabilized; the hybridization equilibrium constants found for the size-matched pores were 2 orders of magnitude larger than those for larger pores (≥3.5 nm).…”
Section: Structural Stability Of Adsorbed Proteinmentioning
confidence: 99%
“…[115][116][117] The results indicated that short-DNA duplexes were stabilized by confinement inside aminefunctionalized cylindrical silica pore channels (BJH pore diameter, 1.6 to 7.4 nm). 115,116 Particularly, short-DNA duplexes confined inside the size-matched pores (BJH pore diameter: 1.6 and 2.3 nm) were significantly stabilized; the hybridization equilibrium constants found for the size-matched pores were 2 orders of magnitude larger than those for larger pores (≥3.5 nm). Since significant stabilization was observed for not only complementary but also single-mismatched DNA duplexes, 115 spatial confinement of the DNA duplex inside the size-matched pore was suggested for the enhanced duplex stability.…”
Section: Structural Stability Of Adsorbed Proteinmentioning
confidence: 99%
“…A perpendicularly oriented cylindrical mesopore channel is favored to create an effective biocatalytic system with an enzyme, but there has been no effective method to synthesize a continuous mesoporous film with perpendicular mesochannels. Yamauchi and co-workers succeeded in forming a continuous mesoporous aluminum oxide (MAO) film composed of vertically oriented nanopillars by using aluminum tri- n -butoxide as the aluminum source. , However, it is expected that a biomacromolecule tightly confined inside a cylindrical mesopore channel exhibits more enhanced stability than that embedded between nanopillars. , Recently, Mou and co-workers reported a simple method to deposit a mesoporous silica film with perpendicular nanochannels. The perpendicular silica-nanochannel can be used for the confinement of positively charged protein molecules, but the electrostatic repulsion between GOD and the silica surface would reject the GOD confinement …”
Section: Introductionmentioning
confidence: 99%
“…17,18 However, it is expected that a biomacromolecule tightly confined inside a cylindrical mesopore channel exhibits more enhanced stability than that embedded between nanopillars. 20,21 Recently, Mou and co-workers reported a simple method to deposit a mesoporous silica film with perpendicular nanochannels. The perpendicular silica-nanochannel can be used for the confinement of positively charged protein molecules, but the electrostatic repulsion between GOD and the silica surface would reject the GOD confinement.…”
Section: ■ Introductionmentioning
confidence: 99%